No Differences of Immune Activation and Microbial Translocation Among HIV-infected Children Receiving Combined Antiretroviral Therapy or Protease Inhibitor Monotherapy. Issue 11 (March 2015) - Falcon-Neyra, Lola; Benmarzouk-Hidalgo, Omar J.; Madrid, Lola; Noguera-Julian, Antoni; Fortuny, Claudia; Neth, Olaf; López-Cortés, Luis; Shu., Yi
<x xml:space="preserve">Abstract</x> Abstract This is a cross-sectional study of 15 aviremic chronic HIV-infected children revealing no differences in immune activation (IA; HLA-DR+CD38+ CD4+ and CD8+ T cells, and sCD14) and microbial translocation (MT; lipopolysaccharides (LPS) and 16S rDNA) among HIV-infected patients under combined antiretroviral treatment (cART; n = 10) or ritonavir-boosted protease inhibitor monotherapy (mtPI/rtv; n = 5). In both cases, IA and MT were lower in healthy control children (n = 32). This observational study suggests that ritonavir boosted protease inhibitor monotherapy (mtPI/rtv) is not associated with an increased state of IA or MT as compared with children receiving cART.